Influencer Marketing Between Mothers: The Impact of Disclosure and Visual Brand Promotion. Issue 3 (28th August 2021) - Holiday, Steven; Densley, Rebecca L.; Norman, Mary S.
Abstract: Mothers are among the original social media influencers and their social media content plays a vital role in supporting and sustaining motherhood through relationships of social exchange while simultaneously supporting brand marketing efforts. This study, then, uses a within-subjects, repeated-measure experimental design to examine how increasing the overtness in the promotional explicitness through the text and images of mother influencers' ( Insta-Moms ) Instagram posts disrupts mother consumers' affective responses toward the messages either directly or indirectly, through perceptions of manipulative intent. Findings indicate adverse response when promotional disclosure was present but brand promotion was less overtly explicit, but when brands were both textually and visually promoted, it assuaged feelings of manipulative intent and enhanced affective response to the posts.